Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3928/01477447-20100625-11
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Metasul Metal-on-Metal Total Hip Arthroplasty

Abstract: We assessed 90 total hip arthroplasties (THAs) performed with the Metasul metal-on-metal hip system (Zimmer, Warsaw, Indiana); the patients were monitored for >10 years. The average Harris Hip Score of the patients was 40.5 points preoperatively and 85.8 points at final follow-up. No adverse reactions to the metal debris were observed in patients presenting with symptoms or phenomena such as unexplained pain, joint effusion, bursitis, or pseudotumor. Radiographically, the acetabular component fixation was stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
4
22
1
Order By: Relevance
“…Our study, in line with recent literature on 28-mm metal-onmetal femoral heads has reported excellent survivorship rates between approximately 91 and 98 % [12][13][14][15][16][17][18][19]. With regards to implant stability, the selected studies have demonstrated six recurrent dislocations requiring revisions in greater than 1,000 hips [12][13][14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study, in line with recent literature on 28-mm metal-onmetal femoral heads has reported excellent survivorship rates between approximately 91 and 98 % [12][13][14][15][16][17][18][19]. With regards to implant stability, the selected studies have demonstrated six recurrent dislocations requiring revisions in greater than 1,000 hips [12][13][14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 89%
“…Published Kaplan-Meier survivorships have been reported as excellent, between 91 and 98 % at long-term follow-up periods [12][13][14][15][16][17][18][19]. Long-term studies are required to support the increased use of MoM bearings in younger patients given their potential deleterious effects.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the Metasul bearing has demonstrated excellent survival in young patients of 100 % at 12 and 99 % at 14 years, respectively [6,7]. Similarly, minimum ten-year survival rates of 94 % and 99 %, have been reported for this articulation in older patients with uncemented THA [5,8]. However, our cohort of young patients could not support these excellent results, demonstrating only an acceptable survival rate of 91 % for all revisions at 13 years.…”
Section: Discussionmentioning
confidence: 54%
“…However, over the past few years severe concerns have been raised in relation to mainly large head diameter MoM articulations with catastrophic softtissue reactions due to excess metal debris, with possible subsequent implant failure [2,3]. In contrast, several studies report acceptable implant failure rates according to the NICE criteria [4] using the 28-mm head Metasul MoM articulation [5][6][7][8][9]. However, there are only few long-term data on the results of primary cementless THA using this articulation in young patients [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported good results with the Metasul at followup of more than 10 years with survival ranging from 81% to 100% (Table 2) [10,12,15,20,22,35,42,43,45]. Two other studies have reported mid-to long-term followup for small-diameter MoM THA devices other than Metasul [36,39].…”
Section: Discussionmentioning
confidence: 99%